New monoclonal antibodies specific for mammalian protamines P1 and P2. (2nd November 2018) - Balhorn, Rod; Steger, Klaus; Bergmann, Martin; Schuppe, Hans-Christian; Neuhauser, Stefanie; Balhorn, Monique C.
ABSTRACT: The expression of protamines and the binding of these small arginine-rich proteins to DNA complete the process of spermatid chromatin reorganization and the global inactivation of the male's haploid genome that occurs during the final stages of sperm development in mammals. While a number of anti-protamine antibodies have been created during the last 40 years, only a few have proven useful for detecting the presence of the protamines, determining the timing of their expression and deposition in chromatin, and investigating their structure and function in both maturing spermatids and sperm. The aim of this effort was to develop an additional set of monoclonal antibodies (MAbs) that not only recognize new P1 and P2 protamine epitopes but also work well as IHC reagents for detecting and identifying mammalian protamines in testicular tissue and ejaculated sperm. Using a combination of native and synthetic human protamines as antigens, 38 hybridoma clones recognizing human protamine P1 or P2 were generated. Antibodies produced by the 12 best clones were screened for selectivity by enzyme-linked immunosorbent assay, and two were found to recognize only human protamine P1 or P2, while a number of the others bound to both the human and mouse proteins. One MAb recognized every protamine tested. All the antibodies, including one recognizing stallion P1 and another recognizing stallion P2, bound to the native protamines in the chromatin of spermatids or sperm. While the majority labeled only elongating spermatids or sperm, several of the antibodies were found to also bind to the cytoplasm or nuclei of cells that lack protamine, which indicates these MAbs must recognize epitopes present in the protamines that are also found in other proteins. Thirteen overlapping human protamine P1 peptides were synthesized and subsequently used to identify the epitopes recognized by the six best antibodies. Abbreviations : BSA: bovine serum albumin; ELISA: enzyme-linked immunosorbent assay; HCl: hydrochloric acid; IHC: immunohistochemistry; i.p: intraperitoneal; LIS: lithium diiodosalicylate; MAb: monoclonal antibody; PBS: phosphate buffered saline